Partisipasi Generasi Millenial dalam Mengawasi Tahapan Pemilu 2024 - Yusrin Yusrin; Salpina Salpina (Departement of Mathematics Education, 2023)
Youth are agents of change who must continue to fight for the principles of the Indonesian state and must be able to manage the democratic transition process in a better direction, especially being able to oversee the implementation of a just political process. For a country to develop, its youth must be of high quality, so one of their vital tasks is political literacy. Therefore, the purpose of this study is to find out how important millennial political behavior and involvement are in influencing millennial political decisions in the 2024 general election. The purpose of this essay is to provide information to readers about how the Millennial Generation will exercise their right to vote on general election in 2024. Using a qualitative approach and literature study methodology, namely by looking for various references on the involvement of Millennial voters in Indonesia, both from books and scientific journals. In terms of maintaining the spirit of democracy so that it continues to grow among the millennial generation, the findings of this study show that the participation of the millennial generation greatly influences the extent to which a candidate can be elected. The outputs and benefits of implementing this socialization are being able to raise early awareness of the younger generation to start being active in the political process, such as exercising their right to vote, becoming election observers, and being able to provide motivation for the younger generation. work directly as a Success Team in supporting potential partners who have a vision and mission that are in line with their views..